PELAKSANAAN SUPERVISI KONTEKSTUAL DALAM PEMBINAAN PROFESIONALITAS GURU BERBASIS BUDAYA PESANTREN - Masnawati, Eli (FKIP Universitas Wisnuwardhana, 2018)
Guidance on the implementation of contextual supervision in the professionalism of the pesantren-based teacher professionalism that must be carried out by the chairman of the foundation and administrators in the pesantren related to the teaching profession based on interesting and unique pesantren culture is discussed with various issues of teacher professional development. This article aims to find out the phenomenology associated with the implementation of contextual supervision in teacher professional development based on the pesantren culture. This research was conducted with a qualitative approach. This study found about (1) the interaction patterns used in coaching namely imtikhan, prayer in congregation, silaturrahmi, regular meetings once a month. (2) approaches in coaching namely groups, individuals, seniority, pesantren bureaucracy. (3) supervision and evaluation, the supervisors and evaluators are the heads of foundations, principals, vice principals, school supervisors, 5 senior teachers and school committees. Follow-up supervision and evaluation of motivation, reinforcement and praise, guidance. Awarding for successful people is in the form of a 100% attendance certificate, additional hours of teaching in Babur Rohmah Middle School and High School, being a homeroom teacher, additional honorariums. Teachers who have not succeeded in getting a book related to teacher professionalism, reduced teaching hours, not being a homeroom teacher, are given a one-month salary.Keywords: coaching, teachers, a boarding school